Chemotherapy‐induced eccrine squamous syringometaplasia in an infant. Issue 1 (12th December 2017) - Bittar, Peter G.; Casady, Megan; Selim, Maria A.; Prose, Neil S.
Abstract: There are few reports of chemotherapy‐induced eccrine squamous syringometaplasia in children. We report the first case of an infant developing this condition after treatment with busulfan, fludarabine, and antithymocyte globulin in preparation for bone marrow transplantation. Twenty‐eight days after transplantation, the infant developed faintly erythematous papules and plaques on the bilateral axillae, inguinal folds, and sites of adhesives. Punch biopsy revealed eccrine glands with dyskeratotic cells and focal squamous metaplasia consistent with chemotherapy‐induced eccrine squamous syringometaplasia.